Therapeutic Potential of IL-17-Mediated Signaling Pathway in Autoimmune Liver Diseases - Haiyan Zhang; Francesca Bernuzzi; Ana Lleo; Xiong Ma; Pietro Invernizzi (Hindawi Limited, 2015)
Emerging evidence reveals that various cytokines and tissue microenvironments contribute to liver inflammation and autoimmunity, and IL-17 family is one of highlights acknowledged. Although the implication of IL-17 family in most common autoimmune diseases (such as psoriasis, inflammatory bowel disease, and rheumatoid arthritis) has been extensively characterized, the role of this critical family in pathophysiology of autoimmune liver diseases (AILD) still needs to be clarified. In the review, we look into the intriguing biology of IL-17 family and further dissect on the intricate role of IL-17-mediated pathway in AILD. Considering encouraging data from preclinical and clinical trials, IL-17 targeted therapy has shown promises in several certain autoimmune conditions. However, blocking IL-17-mediated pathway is just beginning, and more fully investigation and reflection are required. Taking together, targeting IL-17-mediated responses may open up new areas of potential clinical treatment for AILD.